Negotiation and Resilience: Human Resource Management Transformation in Coastal MSMEs of South Sulawesi - Burhanuddin (Journal Management & Economics Review (JUMPER), 2025)
This qualitative study investigates the transformation of Human Resource Management (HRM) practices in community-based MSMEs in the coastal areas of South Sulawesi. Using an exploratory approach with in-depth interviews, observations, and document reviews involving 20 participants, the research reveals five key themes of HRM transformation: (1) negotiated formalization, where formal HR elements are flexibly adopted considering kinship ties; (2) relational performance systems emphasizing collective assessment mechanisms; (3) youth-mediated digital adoption; (4) crisis-driven safety and wellbeing practices; and (5) financing constraints limiting human capital investments. The findings demonstrate that HRM transformation does not follow standard corporate models but rather constitutes a hybridization process where formal practices are adapted within community norms. The study concludes that effective support for coastal MSMEs requires multidimensional approaches that respect local cultural logics, leverage youth as digital mediators, and address structural financing constraints.